Human development in sacred landscapes: between ritual tradition, creativity and emotionality - Käppel, Lutz; Pothu, Basilikē (V&R unipress, 2015)
Memory in stone : ritual lanscapes and concepts of monumentality in prehistoric societies / Bettina Schulz Paulsson -- Greek landscapes : profane and sacred / Oliver Rackham -- Sacred groves : nature between religion , philisophy and politics / Lukas Thommen -- Under the open sky : imagining the Dionysian landscape / Susan Guettel Cole -- Landscape and the cosmos in the Apolline rites of Delphi, Delos and Dreros / Efronsyni Boutsikas -- From Delos to Delphi : how Appolo comes home / Jeremy McInerney -- Barren landscapes and sacrificial offerings in the Homeric hymn to Apollo / Sarah Hitch -- Landscape and females in hte Odyssey : Calypso, Circe and Nausicaa / Mercedes Aguirre Castro -- An orge in three landscapes : cyclops in Homer, Euripides amd Theokritos / Richard Buxton -- Landscape and the magic of music in Pindar's twelfth Pythian ode / Lutz Käppel -- The distribution of cult in the landscape of Eleia / James Roy -- Newbown babies and newborn islands : insularity and politics / Vassiliki Pothou -- A Greek landscape with God and his saints : a case study from the nineteenth and twentieth centuries AD / Hamish Forbes -- The role of archaeological museums in Greece for contemporary societies : approaches and perspectives / Michael Teichmann